장애인근로사업장 발달장애인의 일과 복지서비스경험에 관한 질적 사례연구 - 박정임(Jung Im Park); 김명희(Myung Hee Kim) (한국콘텐츠학회 논문지, 22(5), 2022)
This study is a qualitative case study whose aims were to investigate the work and welfare service experiences of people with developmental disabilities in the occupational rehabilitation facilities. For the purpose of this study selected as its participants 8 people with developmental disabilities whom has been worked currently in the occupational rehabilitation facilities. The profound interviews of those participants were performed and the data on the occupational rehabilitation facilities were analysed. Also, the study analysed the data in a way of investigating the respondents' statements regarding their work and welfare in the occupational rehabilitation facilities. The results of this analysis, 10 categories, 22 sub-categories and 5 key topics of the respondent's experiences were drawn out. The 5 key topics of the people with developmental disabilities in the occupational rehabilitation facilities were 'pride of the economic stability', 'happiness of work itself', 'a sense of accomplishment of the regular worker', 'recognition and exchange of the coworker and superior', 'expectation of the welfare service and the expansion of the participation in the occupational rehabilitation facilities were 'pride of the economic stability', 'happiness of work itself', 'a sense of accomplishment of the regular worker', 'recognition and exchange of the coworker and superior', 'expectation of the welfare service and the expansion of the participation in the occupational rehabilitation facilities'. Based on the results, implications for the work and welfare service of people with developmental disabilities in the occupational rehabilitation facilities were provided. 본 연구에서는 장애인근로사업장 발달장애인의 일과 복지서비스 경험을 질적 사례연구방법을 통해 심층적으로 고찰하고자 하였다. 이러한 연구목적을 달성하기 위하여 국내 G장애인근로사업장내 발달장애인 8명을 대상으로 반구조화된 질문을 활용하여 심층 인터뷰하였으며, 이를 토대로 사례 내 분석과 사례 간 분석을 실시하였다. 또한, 장애인근로사업장의 일과 복지서비스와 관련된 문서자료, 현장관찰, 문헌 검토 등을 실시하고 분석하여 이들의 상호작용을 고찰하였다. 연구결과, 장애인근로사업장 발달장애인의 일과 복지서비스 경험은 총 10개의 구성요소와 22개의 하위구성요소로 도출되었으며, 이를 통해 장애인근로사업장 발달장애인의 일과 복지서비스 경험의 본질은 총 5개로 도출되었다. 장애인근로사업장에서 근무하는 발달장애인의 일과 복지서비스 경험의 본질은 경제적 자립의 안정과 자부심, 일 자체의 즐거움과 책임감, 사회 속에 정규직이라는 성취감, 직장 내 사람들의 인정 및 지지적 교류, 복지지원 및 참여확대에 대한 기대 등으로 나타났다. 본 연구의 결과를 토대로 장애인근로사업장 발달장애인을 위한 일과 복지서비스 지원의 국내 직업재활 정책적 방향과 함의를 제언하였다.